Economics of Tobacco Control in China 2016
DOI: 10.1142/9789813108721_0004
|View full text |Cite
|
Sign up to set email alerts
|

The Healthcare Costs of Secondhand Smoke Exposure in Rural China

Abstract: Objective-The goal of this study was to assess the healthcare costs attributable to secondhand smoke (SHS) exposure among nonsmoking adults (age≥19) in rural China.Methods-We analyzed data from the 2011 National Rural Household Survey which was conducted among adults in five provinces and one municipality in China (N=12,397). Respondents reported their smoking status, health conditions and healthcare expenditures. Relative risks were obtained from published sources. Healthcare costs included annual outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Yang et al, 1999), risk factors (Hesketh, Ding, & Tomkins, 2001; Wang et al, 1994; Wen et al, 2007), health consequences (Gao, Smith, Hammond, & Hu, 2007; Liu et al, 1998; Zhang & Ratcliffe, 1993), and economic burden (Hu & Tsai, 2000; Sung, Wang, Jin, Hu, & Jian, 2007; L. Yang, Sung, Mao, Hu, & Rao, 2011; Yao, Sung, Mao, Hu, & Max, 2014). The prevalence of smoking remained at or above 60% between 1984 and 2002 for Chinese males (Gu et al, 2004; G.…”
mentioning
confidence: 99%
“…Yang et al, 1999), risk factors (Hesketh, Ding, & Tomkins, 2001; Wang et al, 1994; Wen et al, 2007), health consequences (Gao, Smith, Hammond, & Hu, 2007; Liu et al, 1998; Zhang & Ratcliffe, 1993), and economic burden (Hu & Tsai, 2000; Sung, Wang, Jin, Hu, & Jian, 2007; L. Yang, Sung, Mao, Hu, & Rao, 2011; Yao, Sung, Mao, Hu, & Max, 2014). The prevalence of smoking remained at or above 60% between 1984 and 2002 for Chinese males (Gu et al, 2004; G.…”
mentioning
confidence: 99%
“…TSP-induced health risks burden the government and families. It has been reported that the total healthcare cost of TSP exposure in rural China accounted for 0.3% of China's national healthcare expenditure in 2011 [22] . Fortunately, thanks to government policies, cigarettecarton sales decreased gradually from 260.98 billion in 2014 to 233.58 billion in 2018 according to the National Bureau of Statistics [23] .…”
Section: Discussionmentioning
confidence: 99%